Use of life cycle assessment (LCA) to facilitate continuous improvement of on-farm environmental performance : a sheep dairy case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University, Manawatū, New Zealand - Mohan, Raynisha (Massey University, 2018)
Farm management practices have in recent times seen a shift towards a greater focus on sustainable agriculture, concerning environmental impacts and food safety. In New Zealand, the sheep dairy industry has seen rapid growth in the past decade as an alternative dairy source. The importance of sustainability in this industry has been recognised with New Zealand government programmes such as the Primary Growth Partnership, designed to boost the exports of the emerging industry, with a focus on sustainable production. Utilising a Life Cycle Assessment (LCA) based environmental certification scheme as a tool to support continuous improvement of on-farm environmental management can potentially support the emerging sheep dairy industry to define and communicate the sustainability of their farming practices. This research aims to inform the practice of environmental labelling with application to sheep dairy products and offer a way of validating the sustainability statements made by New Zealand sheep dairy producers in their marketing approaches. The two key objectives of the study were (1) to determine the environmental hotspots of New Zealand sheep dairy farming and what mitigation strategies can be developed, and (2) Develop key performance indicators (KPIs) for an LCA-based farm certification system focussed on sheep dairy in New Zealand. To address objective 1, an LCA study was conducted on a New Zealand sheep dairy case-study farm. Sensitivity analysis around the type of imported grain feed and pesticide used were also conducted. To address objective 2, a review was conducting on four existing environmental certification schemes. Following this, a prototype list of KPIs based on the LCA findings was then designed. The LCA study utilised a cradle-to-farmgate boundary and included the following activities: livestock emissions; the production and use of fertiliser, herbicides, and pesticides; production of imported supplementary feed; production and use of fuels and electricity; and lastly emissions from milking shed and effluent. The results showed that both the off-farm and on-farm stages contributed to environmental impacts and the production and use of fertilisers, application of pesticides, and enteric fermentation of livestock were found to be the biggest hotspot areas. A prototype environmental certification scheme comprising a Tier 1 KPI framework was then formulated, combining both the LCA results and previously consolidated indicators. Each KPI was categorised under the following themes: land management, nutrient, pesticide, water management, and lastly, energy and carbon management.
Figures 1 & 2 have been removed for copyright reasons. They may be accessed from these links respectively: http://www.circularecology.com/lca.html & http://dx.doi.org/10.1016/j.scitotenv.2014.09.020
Keywords: Sheep Milking; New Zealand; Case studies; Environmental aspects; Sustainability; Evaluation; Sustainable agriculture; Certification